Causes of corruption in Russia: a disaggregated analysis - Veronika Belousova; Rajeev K. Goel; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper examines determinants of corruption across Russian regions. Key contributions include: (i) a formal study of economic corruption determinants across Russian regions; (ii) comparisons of determinants of perceived corruption versus those of actual corruption; and (iii) studying the influence of market competition and other factors on corruption. The results show that economic prosperity, population, market competition and urbanization are significant determinants of Russian corruption. The use of alternative corruption measures reveals that economic prosperity and population have a largely similar impact on corruption perceptions and corruption incidence. However, there are significant differences in the effects of competition and urbanization.
URN:NBN:fi:bof-201408071926
Keywords: 330